Pengaruh Gaya Kepemimpinan Transformasional Dalam Membangun Budaya Inovasi Dan Meningkatkan Keterlibatan Karyawan Gen Z Di Pt. Alfamart. Tbk - Mayang sari; Amelia sholeha (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This study analyzes the influence of transformational leadership style in building a culture of innovation and increasing the involvement of Gen Z employees at PT. Alfamart. The study is based on the fact that Gen Z, born between 1997 and 2012, has unique characteristics that require a different leadership style than previous generations. Transformational leadership is considered to be able to meet the demands of Gen Z who want an innovative and flexible work environment. This study uses a quantitative method with survey data from 50 respondents of PT. Alfamart Se-Cikarang. Data analysis uses descriptive statistics (SmartPLS) to see the relationship and influence between transformational leadership variables, innovation culture, and employee engagement. The results of the study show that transformational leadership has a positive and significant influence on the culture of innovation and employee engagement. The culture of innovation has also been proven to mediate the relationship bet employee.